Strong reciprocity, cooperation, focal rules and deontological virtues - Largoza, Gerardo L. (Animo Repository, 2007)
Strong reciprocity, or the willingness of players to act as "conditional cooperators" who punish bad behaviour and reward good behaviour may be a more sophisticated explanation for the evolution of cooperation than folk theorems, but critics have argued that it is maladaptive and thus unable to account for the survival of cooperation within large, motivationally heterogenous populations. Antoci & Zarri's evolutionary model based upon the interaction of certain "focal types" shows the conditions under which survival becomes possible - but concludes somewhat disturbingly that altruistic rewarding and punishing behaviour ("strong reciprocation") leads to a social equilibrium in which all agents become selfish. I examine the logic of their main arguments with reference to two other models of other-regarding preferences and conclude that in each case, there is a reason to investigate the role of "deontological" virtues and focal rules.